Temporal Organization of the Sleep-Wake Cycle under Food Entrainment in the Rat - Castro-Faúndez, Javiera (Sleep, 2016)
STUDY OBJECTIVES: To analyze the temporal organization of the sleep-wake cycle under food entrainment in the rat. METHODS: Eighteen male Sprague-Dawley rats were chronically implanted for polysomnographic recording. During the baseline (BL) protocol, rats were recorded under a 12:12 light-dark (LD) schedule in individual isolation chambers with food and water ad libitum. Food entrainment was performed by means of a 4-h food restriction (FR) protocol starting at photic zeitgeber time 5. Eight animals underwent a 3-h phase advance of the FR protocol (A-FR). We compared the mean curves and acrophases of wakefulness, NREM sleep, and REM sleep under photic and food entrainment and after a phase advance in scheduled food delivery. We further evaluated the dynamics of REM sleep homeostasis and the NREM sleep EEG delta wave profile. RESULTS: A prominent food-anticipatory arousal interval was observed after nine or more days of FR, characterized by increased wakefulness and suppression of REM sleep propensity and dampening of NREM sleep EEG delta activity. REM sleep exhibited a robust nocturnal phase preference under FR that was not explained by a nocturnal REM sleep rebound. The mean curve of sleep-wake states and NREM sleep EEG delta activity remained phase-locked to the timing of meals during the A-FR protocol. CONCLUSIONS: Our results support the hypothesis that under food entrainment, the sleep-wake cycle is coupled to a food-entrainable oscillator (FEO). Our findings suggest an unexpected interaction between FEO output and NREM sleep EEG delta activity generators. CITATION: Castro-Faúndez J, Díaz J, Ocampo-Garcés A. Temporal organization of the sleep-wake cycle under food entrainment in the rat. SLEEP 2016;39(7):1451–1465.